Plant extract as antimicrobial agent (Indian Journal of Arid Horticulture, 2025)
Several plants have been evaluated for possible Antimicrobial activity and to get remedy from a variety of ailment of microbial origin. Certain plants contain products such as alkaloids, tannins, quinons, essential oil phenol compound and mercuric compound in their extracts. These compounds are known for their antimicrobial activity. In the present study plant extract of various wild species were used as antimicrobial agent. Impregnated discs of the above wild species were prepared using concentrated leaf extract. These discs were used as antibiotic agent against different bacterial species.
Keywords: microbial; antimicrobial; quinons; ailment; alkaloids